2021
DOI: 10.1002/wmh3.437
|View full text |Cite
|
Sign up to set email alerts
|

The association between media exposure and enrollment in health insurance in Nepal: Implications for health policy

Abstract: Exposure to mass media plays a crucial role in behavior change or decision‐making. The study used a cross‐sectional survey design. A total of 810 households were randomly selected for data collection by using a validated interview schedule. The study examined exposure to radio, television (TV), hoarding boards (billboards), newspapers, and brochures, pamphlets, and posters as media platform “independent variables” and enrollment in health insurance (HI) as the “dependent variable.” Data showed that 60% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
2
3
0
Order By: Relevance
“…The ndings of the multivariate regression analysis revealed that media exposure, MPCE, and education all signi cantly affect HI enrolment. The ndings of this study are likewise in line with those of numerous other studies conducted in Ghana [25,36], Nepal [24], South Korea [37], Kenya [38,39], and India [40],…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The ndings of the multivariate regression analysis revealed that media exposure, MPCE, and education all signi cantly affect HI enrolment. The ndings of this study are likewise in line with those of numerous other studies conducted in Ghana [25,36], Nepal [24], South Korea [37], Kenya [38,39], and India [40],…”
Section: Discussionsupporting
confidence: 92%
“…The ndings based on Ghana's Demographic and Health Survey (2014) highlighted the positive association between enrolment in the country's National Health Insurance Scheme (NHIS-2003) and mass media exposure [25]. A review of the literature reveals that those who got information related to HI from radio, TV, and hoarding had 1.91 times, 1.72 times, and 1.87 times higher likelihoods of being enrolled in HI respectively [24]. Further, a study conducted before launching three mega community health insurance schemes in India reveals that increasing awareness is one of the important preconditions for voluntary enrolment in those government schemes [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our study, exposure to media, socioeconomic rank and the level of education had the greatest contribution to inequality in coverage with any type of health insurance in SSA [2]. A study conducted in Nepal, Ghana and Ethiopia also found that mass media exposure was significantly associated with high enrollment in HI [15] [16] [17] [18]. This has implications in utilization of the various media communication channels in making strategic communication plans to promote health insurance uptake in Malawi or any other similar settings.…”
Section: Resultssupporting
confidence: 85%